HUBUNGAN DAN PERAN PEMANGKU KEPENTINGAN POGRAM SMART-KAMPUNG KABUPATEN BANYUWANGI - Ella Lesmanawaty' Wargadinata (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2021)
There is a deep understanding that Electronic Government implementation in developing countries has a vast difference in developed countries' performance. The stakeholder’s role have a significant influence in ensuring the sustainability of e-government deployment. The paper reveals the success story of The Smart-Kampung as an E-government model for rural in Banyuwangi that has achieved the remarkable transformation from banal-rural to the digital society. From the low-level education people who most heavily trust in mystical things and close with black magic practices, from the santet to the internet fans. The paper focuses on identifying the role and the relationship among stakeholders through interviews, observations, previous works and analysis with the NVivo program. Result finding shows how The Banyuwangi regency to set up a proper stakeholders and role’s due to each interest to reach the government's agencies' efficiency and provide benefits to the rural. The Smart Kampung shows the transformation of traditional bureaucracy processes into information communication and technology services. It is engaging in reaching a transformational society beyond the online administration of rural services per se. The results showed that smart villages' key success factors lie in a shared responsibility among various stakeholders. The political leaders come as an axis in the stakeholder relationship model. Keywords: E-Government stakeholders, online public services, conventional bureaucracy, political Leadership